Cover Feature: Synergistic Effects in the Activity of Nano‐Transition‐Metal Clusters Pt12M (M=Ir, Ru or Rh) for NO Dissociation (ChemPhysChem 21/2022). Issue 21 (4th November 2022) - Vekeman, Jelle; Wang, Qing; Deraet, Xavier; Bazin, Dominique; De Proft, Frank; Guesmi, Hazar; Tielens, Frederik
Abstract : The Cover Feature shows NO molecules adsorbed on four different M13  clusters prior and after NO dissociation. Doping Pt13  with Ru, Rh or Ir stabilizes NO adsorption and lowers activation energies of the DeNOx process, pictorially represented by mountainous terrain surrounding the process. Cover design by Dr. Jelle Vekeman. More information can be found in the Research Article by Jelle Vekeman, Frederik Tielens and co‐workers .